ANALISIS PERBANDINGAN KINERJA BANK PEMERINTAH DAN BANK SWASTA DI INDONESIA - Octifane, Witra; ', Hardi; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims is to find the differences between government bank and private bank performance in Indonesia toward Capital Adequacy Ratio (CAR), Non Performing Loan, Return on Equity (ROE), Return on Asset (ROA), Operational Expense to Operational Revenue (BOPO) and Loan to Deposits Ratio (LDR).The population of this research are all government and private bank at the Indonesia Stock Exchange. The sampling technique used in this study was purposive sampling because only a selected sample met the criteria only. Analysis techniques use descriptive analysis and paired t test.The result of this study are : there were differences in government and private bank performance for ratio CAR, NPL, ROE, BOPO dan LDR. But there is no differences for ROA. According to the Paired T-Test it has a significant difference at CAR, ROE, BOPO, LDR and NPL in the period of 2010 until 2012. Meanwhile for ROA there is no significant differences. Government bank financial ratio have a good and higher value from the private bank, it means that government bank have a good performance from private bank.Key Word : Capital Adequacy Ratio (CAR), Non Performing Loan,, Return on Equity (ROE), Return on Asset (ROA), Operational Expense to Operational Revenue (BOPO), Loan to Deposits Ratio (LDR).